EFFECTS OF APPLE AND ORANGE JUICES ON VIABILITY OF REFRIGERATED GOAT SEMEN - ABIOJA, MONSURU OLADIMEJI (Journal of Agricultural Sciences (Belgrade), 2018)
This study investigatedthe effects of apple and orange juiceson viability of refrigerated spermatozoa of West African Dwarf (WAD) goat bucks.Pooled semen samples fromWAD goat bucks were diluted with Tris-egg yolk extenderseachsupplemented with apple and orangejuices at 0, 2.5, 5, 7.5 and 10/100 mL of diluents. The diluted semen samples were assessed for sperm viability and malondialdehyde (MDA) concentrationafter in vitro storage for 240 hours at 5oC. The ability to maintain sperm motility was higher in extenders supplemented with 7.5% orange juice followed by 10% apple juice compared to other treatments (P